2003
DOI: 10.5703/1288284313257
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Bridge Deck Cracking in Various Bridge Superstructure Systems

Abstract: Prepared in cooperation with the Indiana Department of Transportation and Federal Highway Administration. AbstractMany bridges in the state of Indiana have been identified to have cracking in the concrete deck. Cracking has been identified in the negative and positive moment regions of bridges on both the top and bottom surfaces and can appear before or shortly after the opening of the structure to live loads. Significant crack widths and various degrees of cracking exist in different bridge systems including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 4 publications
1
40
0
Order By: Relevance
“…Therefore, the top of the deck tends to shrink more than the bottom. This differential shrinkage causes the deck to curl, which is resisted by the composite action of the deck and the superstructure (Frosch et al 2003). Restrained curling introduces higher stresses in the upper portion of the deck than would otherwise be observed due to shrinkage alone (Krauss and Rogalla 1996).…”
Section: Stay-in-place Formsmentioning
confidence: 99%
“…Therefore, the top of the deck tends to shrink more than the bottom. This differential shrinkage causes the deck to curl, which is resisted by the composite action of the deck and the superstructure (Frosch et al 2003). Restrained curling introduces higher stresses in the upper portion of the deck than would otherwise be observed due to shrinkage alone (Krauss and Rogalla 1996).…”
Section: Stay-in-place Formsmentioning
confidence: 99%
“…With this economy from the use of reduced reinforcement steel, many highway agencies preferred to use the empirical method. However, immediate cracks formation have been noticed in many USA bridges [45,46,47,48,49,50,51] prior to opening to traffic, though there is no any evidence that the system would resist other load combinations like thermal and shrinkage stresses. Petrou and Perdikans [52] reported that total deflection of bridge deck is not really flexural but also highly influenced by small girder spacing and/or large deck thickness.…”
Section: Conventional Design Methodsmentioning
confidence: 99%
“…Numerous factors can lead to transverse deck cracking in highway bridges including time dependent material properties, restraints, casting sequence, formwork, and environmental factors. Several studies investigated the issue of deck cracking (ACI 2001;Altoubat and Lange 2000;Cady et al 1971;Eppers et al 1998;Frosch et al 2003;Krauss and Rogalla 1996;PCA 1970;Purvis et al 1995;Saadeghvaziri and Hadidi 2002;Schmitt and Darwin 1995;Xi et al 2003). Also, the development of cracking increases the effect of freeze and thaw cycles, which may lead to spalling of concrete and thus resulting in corrosion of steel reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…From a research sponsored by the Indiana Department of Transportation, researchers conducted a field study and constructed laboratory specimens to investigate the behavior of transverse cracks (Frosch et al 2003). Using these specimens, the researchers evaluated the effect of differing bridge deck designs on the control of overall shrinkage and evaluated the contribution of stay-in-place (SIP) steel forms to the formation of transverse cracking.…”
Section: Introductionmentioning
confidence: 99%